Effect of various refining processes for Kenaf Bast non-wood pulp fibers suspensions on heat transfer coefficient in circular pipe heat exchanger - Ahmed, Syed Muzamil; Kazi, Salim Newaz; Khan, Ghulamullah; Sadri, Rad; Dahari, Mahidzal; Zubir, Mohd Nashrul Mohd; Sayuti, Mohd; Ahmad, Pervaiz; Ibrahim, Rushdan (Springer Verlag (Germany), 2018)
Heat transfer coefficients were obtained for a range of non-wood kenaf bast pulp fiber suspensions flowing through a circular pipe heat exchanger test loop. The data were produced over a selected temperature and range of flow rates from the flow loop. It was found that the magnitude of the heat transfer coefficient of a fiber suspension is dependent on characteristics, concentration and pulping method of fiber. It was observed that at low concentration and high flow rates, the heat transfer coefficient values of suspensions were observed higher than that of the heat transfer coefficient values of water, on the other hand the heat transfer coefficient values of suspensions decreases at low flow rates and with the increase of their concentration. The heat transfer were affected by varying fiber characteristics, such as fiber length, fiber flexibility, fiber chemical and mechanical treatment as well as different pulping methods used to liberate the fibers. Heat transfer coefficient was decreased with the increase of fiber flexibility which was also observed by previous researchers. In the present work, the characteristics of fibers are correlated with the heat transfer coefficient of suspensions of the fibers. Deviations in fiber properties can be monitored from the flowing fiber suspensions by measuring heat transfer coefficient to adjust the degree of fiber refining treatment so that papers made from those fibers will be more uniform, consistent, within the product specification and retard the paper production loss.